Development of Mathematical Model to Predict the Removal Rate of Zinc in Zinc Barrel Plating wash water using Full Factorial Design (International Journal of Engineering and Computer Science, 2017)
This study highlights the features of the development of inclusive mathematical models for correlating the interactive and higher order manipulates of the various parameters in the zinc barrel plating wash water. Full Factorial technique is used to perform the experiments. The response factors namely initial concentration, current density and time were involved by zinc removal rate in the zinc barrel plating wash water has been considered and examined. Analysis of variance (ANOVA) was employed to ensure the adequacy of the models so developed and student’s t-test was utilized to check the significance of each factor to appear the final form of the mathematical models. The models so developed are utilized to conclude the values of the response parameters which influence the zinc barrel plating for each given set of variables within the ranges selected.